Generative Learning and the Making of Ethical Space: Indigenizing Forest School Teacher Training in Wabanakik - Koller, Katalin Doiron; Rasmussen, Kay (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
This reflection on community-driven research in process is written from the perspective of graduate student co-researchers collaborating with Wabanaki community co-researchers on a pilot project involving a Wabanaki and a non-Indigenous organization. Three Nations Education Group Inc. (TNEGI) represents three Wabanaki schools and communities in Northeast Turtle Island. The Child and Nature Alliance of Canada (CNAC) offers a Forest and Nature School Practitioner Course (FNSPC) for educators seeking to operate forest schools. These diverse organizations have developed a pilot FNSPC training for a group of TNEGI educators, with the purpose of Indigenizing the FNSPC. This is necessary to address the Eurocentric forest and nature school practices in Canada, which often fail to recognize the herstories, presence, rights, and diversity of Indigenous Peoples and places. TNEGI educators envision a land-based pedagogy that centers Wabanaki perspectives and merges Indigenous and Western knowledges. In the FNSPC pilot, the co-researchers generated course changes as they progressed through the pilot, decolonizing the content and format as they went. Developing this Indigenized version of the FNSPC will have far-reaching implications for the CNAC Forest School ethos and teacher training delivery. This essay maps our collaborative efforts thus far in creating an ethical research space within this Indigenous/non-Indigenous research initiative and lays out intentions for the road ahead.